Climate change and sustainable development issues: arguments and policy initiatives - Rasiah, Rajah; Kari, Fatimah; Sadoi, Yuri; Mintz-Habib, Nazia (Taylor & Francis, 2018)
Global warming has emerged as one of the most serious threats to the existence of humankind. There is also increasing acknowledgement that old arguments that focused on the exhaustion of economic resources and changing dynamics of utility are no longer necessary and useful in confronting climate change. This article reviews the main arguments that have shaped recent global initiatives on mitigating climate change and global warming. The increasing introduction of climate change mitigation initiatives comes from the recognition that such initiatives no longer require reducing economic growth. Fortunately, recent developments appear promising as the majority of the world's nations pledged at the Paris Accord of 2015 to check environmental degradation. Consequently, individual signatories have supplied intended national determined contribution proposals to the United Nations Framework Convention for Climate Change to cap temperature rise to 1.5 ˚C over the next century.